Discursive Power in Contemporary Media Systems: A Comparative Framework. (October 2019) - Jungherr, Andreas; Posegga, Oliver; An, Jisun
Contemporary media systems are in transition. The constellation of organizations, groups, and individuals contributing information to national and international news flows has changed as a result of the digital transformation. The "hybrid media system" has proven to be one of the most instructive concepts addressing this change. Its focus on the mutually dependent interconnections between various types of media organizations, actors, and publics has inspired prolific research. Yet the concept can tempt researchers to sidestep systematic analyses of information flows and actors' differing degrees of influence by treating media systems as a black box. To enable large-scale, empirical comparative studies aimed at identifying interdependencies and power relationships in contemporary media systems, we propose the concept of discursive power. This describes the ability of contributors to communication spaces to introduce, amplify, and maintain topics, frames, and speakers, thus shaping public discourses and controversies that unfold in interconnected communication spaces. We also provide a theoretical framework of how structural features of organizations and media systems contribute to the emergence of discursive power for different types of actors in various contexts. This adds to the theoretical toolkit available to researchers interested in the empirical analysis of contemporary media systems.